Restaurant concepts, management and operations - John R. Walker (2023)
The Eighth Edition of Walker’s, Restaurant Concepts, Management, and Operations continues the success of previous editions, providing, in an easy-to-read way, all of the skills and information needed to master every challenge and succeed in this highly competitive and rewarding industry. Each chapter has been revised, updated, and enhanced with numerous industry examples, sidebars, charts, tables, photographs, and menus. All of this information will help restaurant owners make the decisions necessary to build a thriving business.